Join the IDNLearn.com community and start exploring a world of knowledge today. Our platform offers detailed and accurate responses from experts, helping you navigate any topic with confidence.

What is the determinant of the coefficient matrix of the system?

[tex]\[
\begin{cases}
4x - 6y + 0z = -7 \\
3x + 3y + 0z = -2 \\
2x - 12y + 0z = -1
\end{cases}
\][/tex]

A. [tex]\(-7\)[/tex]

B. [tex]\(-2\)[/tex]

C. [tex]\(-1\)[/tex]

D. [tex]\(0\)[/tex]


Sagot :

To find the determinant of the coefficient matrix of the given system of equations, we follow these steps:

The system of equations is:
[tex]\[ \begin{cases} 4x - 6y + 0z = -7 \\ 3x + 3y + 0z = -2 \\ 2x - 12y + 0z = -1 \end{cases} \][/tex]

The coefficient matrix for this system is:
[tex]\[ \begin{pmatrix} 4 & -6 & 0 \\ 3 & 3 & 0 \\ 2 & -12 & 0 \end{pmatrix} \][/tex]

Next, we need to find the determinant of this 3x3 matrix. The general formula for the determinant of a 3x3 matrix [tex]\(\begin{pmatrix} a & b & c \\ d & e & f \\ g & h & i \end{pmatrix}\)[/tex] is given by:
[tex]\[ \text{det} = a(ei - fh) - b(di - fg) + c(dh - eg) \][/tex]

For our specific matrix, the calculation would be:
[tex]\[ \text{det} = 4(3 \cdot 0 - (-12) \cdot 0) - (-6)(3 \cdot 0 - 2 \cdot 0) + 0(3 \cdot (-12) - 2 \cdot 3) \][/tex]

Simplifying each term:
- The first term is: [tex]\(4(0) = 0\)[/tex]
- The second term is: [tex]\(-6(0) = 0\)[/tex]
- The third term is: [tex]\(0\)[/tex]

Adding these up:
[tex]\[ \text{det} = 0 + 0 + 0 = 0 \][/tex]

Therefore, the determinant of the coefficient matrix is:
[tex]\[ \boxed{0} \][/tex]